2014
DOI: 10.1364/oe.22.028934
|View full text |Cite
|
Sign up to set email alerts
|

Passively Q-switched Nd:YAlO_3 nanosecond laser using MoS_2 as saturable absorber

Abstract: We report on the first passively Q-switched Nd:YAlO₃ laser at ~1079.5 nm using MoS₂ as saturable absorber. The MoS₂ saturable absorber is fabricated by transferring the liquid-phase-exfoliated MoS₂ nanosheets onto a BK7 glass substrate. By inserting the glass MoS₂ saturable absorber into a plano-concave Nd:YAlO₃ laser cavity, we obtain a stable Q-switched laser operation with a maximum average output power of 0.26 W corresponding to a pulse repetition rate of 232.5 kHz, a pulse width of 227 ns and a pulse ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…It has been suggested that this sub-bandgap absorption, unexpected in perfect MoS 2 crystals, results from edge states, similar to an earlier observation on lithographically patterned/microcrystals of MoS 2 with high edge to surface area ratio [36]. Solution-exfoliated MoS 2 is therefore an attractive material for wideband pulse generation in the infrared and potentially, in the visible region, with recent results demonstrating pulse generation from 1030 to 2100 nm, in both discrete and tunable setups [26][27][28][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44]. Similarly, broad tunability has been demonstrated with other TMDs such as molybdenum diselenide (MoSe 2 ) [13], and WS 2 [14], suggesting that TMDs form a diverse group of materials for ultrafast pulse generation.…”
mentioning
confidence: 99%
“…It has been suggested that this sub-bandgap absorption, unexpected in perfect MoS 2 crystals, results from edge states, similar to an earlier observation on lithographically patterned/microcrystals of MoS 2 with high edge to surface area ratio [36]. Solution-exfoliated MoS 2 is therefore an attractive material for wideband pulse generation in the infrared and potentially, in the visible region, with recent results demonstrating pulse generation from 1030 to 2100 nm, in both discrete and tunable setups [26][27][28][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44]. Similarly, broad tunability has been demonstrated with other TMDs such as molybdenum diselenide (MoSe 2 ) [13], and WS 2 [14], suggesting that TMDs form a diverse group of materials for ultrafast pulse generation.…”
mentioning
confidence: 99%
“…In the above situation using GNRs as a SA, the achievable maximum pulse energy was 19 J, which was higher than the results obtained both from the GNRs-based Q-switched Er fiber lasers [8], [9] and some emerging SAs Q-switched 1 m solid-state lasers (such as carbon nanotubes, graphene, topological insulator, and MoS 2 [16]- [19]). However, the generated pulses from such a GNRs-based passively Q-switched laser were in the microsecond region, which is attributed to the small effective modulation depth of GNRs-based SA.…”
Section: Resultsmentioning
confidence: 58%
“…Compared to the fiber laser, solid state laser is much more suitable for highenergy short pulses generation because of less nonlinear pulsesplitting. However, the study of MoS 2 SA on solid state laser has been less addressed [14,15]. To the best of our knowledge, no tunable Q-switched solid state laser has been reported with MoS 2 SA.…”
Section: Introductionmentioning
confidence: 99%